Antioxidative peptides derived from food proteins - Agyei, D.; Danquah, Michael; Sarethy, I.; Pan, S. (2015)
© Springer India 2015. The search for natural antioxidants is an ongoing endeavour as an aid to combat the harmful effects of free radicals. Research advances in the past few decades have shown that, by controlled enzymatic hydrolysis, natural antioxidants can be produced from food proteins. In this chapter, the role of certain antioxidative peptides derived from food proteins is discussed in relation to their prospect in the prevention of oxidative stress. The molecular diversity of these food peptides is described together with their pharmacological effects and mechanisms of action in relation to antioxidation. The production of these peptides and the elucidation of their antioxidative peptides are also presented. Owing to their therapeutic potential, antioxidative peptides derived from food proteins can be incorporated as ingredients in functional foods, nutraceuticals and pharmaceuticals, where their biological activities may inhibit product oxidation or assist in the control and prevention of diseases induced by free radicals. However, further insightful research is needed to overcome certain scientific challenges and thereby increase and promote consumer acceptance of these natural antioxidants.